Airborne Laser Altimeter, Global Positioning System (GPS), Inertial Measurement Unit (IMU) and Imagery Campaign of the Surging Negribreen Glacier, Svalbard, in July 2017 and July 2018 - Ute Herzfeld; Thomas Trantow (Arctic Data Center)
**Data files are available at: [https://arcticdata.io/data/10.18739/A2QF8JK7T/](https://arcticdata.io/data/10.18739/A2QF8JK7T/)** Negribreen, one of largest glaciers in Svalbard, began surging in 2016 and continues to move at relatively fast speeds through 2021. Negribreen has not surged since 1935-1936 and hence there is no modern study on its surge dynamics. A surge-type glacier cycles quasi-periodically between a long quiescent phase of normal flow and a short surge phase when ice speeds increase by a factor of 10-200 times that of quiescence. The rapid ice-acceleration leads to a viscous cycle of wide spread crevassing, rapid advance, and increased calving that lead to catastrophic ice loss and frontal retreat. During the peak surge period in the 2017, the ice loss from Negribreen is estimated to have contributed 5-1.0% of total annual global sea-level rise. During our project, we collected laser altimeter, Global Positioning System (GPS), Inertial Measurement Unit (IMU), image and video data from small helicopter, to obtain high-resolution elevation data suitable for process studies and to complement satellite data. This data package includes the field data from two of our campaigns in July 2017 (negri\\_2017) and July 2018 (negri\_2018). Within each of these subdirectories, are folders containing each our data sets for the given campaign: (1) The 400 hertz (Hz) raw 905 nanometer (nm) laser altimeter data from LaserTech's Universal laser System (ULS) along with an error logfile (laser), (2) Handheld image data from a Nikon D5100 (D5100), and two Nikon Coolpix cameras (L120-1 and L120-2), (3) 1-Hz GPS data from a simple USB-connected GPS receiver (button\_GPS), (4) 10-Hz raw and processed GPS data from a base (Trimble NetR9) and rover (Septentrio APS-3G) kinematic GPS system borrowed from UNAVCO (gps\_unavco) (2018 only), (5) 1-Hz IMU data from a LORD 3DM-GX5-15 Virtual Reference Unit (imu), (6) 2-Hz imagery from a GoPro Hero-5 mounted on the underside of the helicopter (gopro) (2018 only) and (7) Video data from an Aiptex video camera (video-aiptex) (2017 only). A README file is included at the top of the directory structure that specifies the data format for each data type. Each campaign consisted of two successful flights and each of the data subfolders above contain additional subfolders labeled Flight1 or Flight2. A data set may be missing data for a given flight due to instrument failure (e.g. IMU data for Flight1 in 2017 and GoPro imagery for Flight1 in 2018). We were not able to reach Negribreen during Flight 1 of 2018 due to an approaching storm, so instead we collected data from Hayesbreen and Peterman Glacier, which lie just south of Negribreen, but were not currently surging. Some flights include photographic documentation of Tunabreen and other glaciers along the transit flight to Negribreen.